Robust Target Detection and Estimation for Airborne STAP Radar With Arbitrary Array Errors and Target Uncertainty - Jianxin Wu; Yang Zhao; Changxian Li; Peng Shen (IEEE Access, 2025)
In the presence of arbitrary array errors and angle mismatch, performance on target detection and angle estimation will be degraded due to steering vector mismatch. Thus, a robust target detection and estimation algorithm for airborne STAP radar is developed. First, utilizing the spatial-temporal coupling property of the ground clutter, array steering vectors are well estimated by fine Doppler localization of the mainlobe clutter. Then, the robust subspace detector spanned by these estimated array steering vectors is developed, which can improve the detection performance for the targets not located in the look direction. Finally, target angle estimation using subspace coefficients, which implements the ML estimator in a reduced-dimensional version, is presented to reduce the computational complexity of the ML estimator. Numerical examples are given to demonstrate the effectiveness of the presented algorithm.